2002
DOI: 10.1016/s0014-5793(02)03782-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of anArabidopsismitochondrial succinate–fumarate translocator

Abstract: Complementation of a yeast acr1 mutant carrying a deletion of the succinate/fumarate carrier gene enabled functional identification of a mitochondrial succinate translocator from Arabidopsis thaliana (AtmSFC1). Thus complementation of yeast mutants is applicable also for identification and characterization of organellar transporters. Reverse transcription polymerase chain reaction and promoter-GUS fusion showed expression of AtmSFC1 in 2 day old dark grown seedlings, which declined in cotyledons during further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 31 publications
4
69
1
Order By: Relevance
“…5) showed a progressive significant increase in the transcript level of isocitrate lyase (the enzyme responsible for the conversion of isocitrate to succinate and glyoxylate during glyoxysomal fatty acid degradation by b-oxidation) during the period of reserve accumulation. The recent identification of a mitochondrial succinate fumarate transporter (Catoni et al, 2003) and evidence that glyoxysomal activity associated with oil degradation is up-regulated during the late stages of seed maturation (Chia et al, 2005), are in keeping with the results obtained from this study.…”
Section: Functions Of the Mitochondria And Glyoxysome During Seed Matsupporting
confidence: 91%
“…5) showed a progressive significant increase in the transcript level of isocitrate lyase (the enzyme responsible for the conversion of isocitrate to succinate and glyoxylate during glyoxysomal fatty acid degradation by b-oxidation) during the period of reserve accumulation. The recent identification of a mitochondrial succinate fumarate transporter (Catoni et al, 2003) and evidence that glyoxysomal activity associated with oil degradation is up-regulated during the late stages of seed maturation (Chia et al, 2005), are in keeping with the results obtained from this study.…”
Section: Functions Of the Mitochondria And Glyoxysome During Seed Matsupporting
confidence: 91%
“…2C) as are also most of the fatty acid degradation enzymes 17 reflecting the importance of a continuous supply of energy for relocalization of nutrients to reproductive parts. The PP2A-B'z holoenzyme may possibly be involved in the regulation of the mitochondrial succinate/fumarate translocator, 18 or affect the enzymes that are involved in the succinate conversion into malate. This needs further investigation.…”
Section: Evidence For B'z Involvement In Regulation Of Energy Metabolismmentioning
confidence: 99%
“…In recent years several of these transporters have been cloned and investigated at the molecular and biochemical level (22,(31)(32)(33)(34). These studies revealed that some members of the MCF in plants can be present in the plastid membranes (35)(36)(37).…”
mentioning
confidence: 99%